Trichouropoda turcicaovalis sp. nov., a new uropodine mite (Acari: Mesostigmata: Trematuridae) from Turkey - Bal, Durmu A.; Özkan, Muhl (Zootaxa, 2006)
Trichouropoda turcicaovalis sp. nov. (Acari : Trematuridae) is described and illustrated on the basis of specimens collected from Turkey. The protonymph, deutonymph and adult of the new species are described, and an identification key for all 45 species of the Trichouropoda ovalis species group is presented.